FORMATION OF MATHEMATICAL SKILLS OF PRE-SCHOOLERS AND PRIMARY CLASS STUDENTS AS A CONDITION FOR THE FORMATION OF THEIR MATHEMATICAL COMPETENCE - Довгий, Олег (Modern engineering and innovative technologies, 2022)
The article is devoted to the problem of the formation of mathematical competence of students of preschool and primary education. It was concluded that primary mathematics education should be carried out on the principles of partnership, continuity, and p